Atypical megaloblastic anemia: mimicking myelodysplastic syndrome and presenting as heart failure - Thomas, Arppana; Rajeev, Akhil; Chandran, Jinu; Praseeda; Thomas, Merin (International Journal of Research in Medical Sciences, 2025)
Megaloblastic anemia is a reversible hematological disorder caused by impaired DNA synthesis, most commonly due to vitamin B12 or folate deficiency. Mostly it presents with anemia, neuropathy but severe cases can mimic bone marrow failure syndrome or even heart failure-like symptoms. We report a case of a 57-year-old male who presented with progressive fatigue, tingling sensations, and exertional breathlessness. Examination revealed pallor, glossitis, knuckle hyperpigmentation, and peripheral neuropathy. Laboratory investigations showed pancytopenia with a dimorphic blood picture and hypersegmented neutrophils. A positive direct coombs test (DCT) and persistent anemia even after packed red blood cell transfusion initially raised possibility of myelodysplastic syndrome (MDS). However, a markedly low serum vitamin B12 level and megaloblastic changes in peripheral smear and normal bone marrow finding confirmed the diagnosis of vitamin B12 deficiency. Our patient responded dramatically to parenteral vitamin B12 therapy, with rapid improvement. This case highlights the importance of considering nutritional deficiencies in patients with pancytopenia and atypical systemic features. Early recognition and treatment can prevent misdiagnosis, avoid unnecessary interventions, and prevent irreversible neurological complications.